EVALUATION OF BEAUVERIA BASSIANA FOR ITS ANTIBACTERIAL POTENTIAL - SMRITI SEN,; SMRITI SEN,; HARSHITA SHUKLA,; SARDUL SINGH SANDHU, (International Journal of Pharma and Bio Sciences, 2015)
Most of the pathogenic bacterial strains have developed resistance against the commonly used antibacterial drugs. This problem is increasing at an alarming rate and has urged upon the need to search for novel antibacterial compounds from natural sources. Entomopathogenic fungi have proved to be very promising candidates as they are known to produce a vast array of bioactive compounds. Screening the antibacterial potential of such compounds has lead to the discovery of efficiently active compounds in past researches. But the entomopathogenic flora needs to be explored more for such compounds. Therefore, the focus of this study was to determine the antibacterial activity of secondary metabolite of Beauveria bassiana using the agar well diffusion method. It was found that secondary metabolite exhibited maximum antibacterial activity after 21 days of incubation. The activity was highest against Escherichia coli MTCC 1679 and was good against Pseudomonas aeruginosa MTCC 6204 and Bacillus subtilis MTCC 441. But it was poor against Salmonella typhi MTCC 733. The zones of inhibition obtained against them were 30mm, 24mm, 18mm and 6mm respectively. However no activity was expressed against Klebsiella pneumoniae MTCC 4032. Thus results of this research work reveal that entomopathogenic fungal isolate Beauveria bassiana could be used for production of broad spectrum and eco-friendly antibacterial compounds.